Localism and marks of distinction in cuban art of the 90´s (2006)
Throughout the 20th century, Cuban art incorporatednew concepts such as those of localism and Cubanism.These topics were discussed in different ways accordingto the social, political, economic and cultural situationsthe country was experiencing up to the last decade of thecentury. At this time, critical distinctions are associatedwith these terms and they acquire new meanings. Theseconcepts will be illustrated through some examples of thework of artists such as Carlos Garaicoa, Tania Brugueraand the Gabinete Ordo amoris group.